Between e-culture and real culture: a peep through the lenses of Nollywood - Abakporo, Princewill; Samuel, Gloria (Pedagogika Społeczna Nova, 2023)
E-culture otherwise referred to as electronic culture has become a robust field of study especially in understanding its trajectories and intersections with politics, economy, propaganda, education, culture, and arts. The term which generally captures everything that can be classified as online or digital culture has become a dominant factor in (re)imaging, projecting, and influencing opinions about individuals, ideologies, policies, culture, and arts. It has also fueled debates about fidelity between what is projected online and the reality of the situation offline especially as seen in Nollywood films. This work pilfers from the canons of Cultivation and Spiral of Silence theories, to investigate the fidelity of Nollywood as e-culture to Igbo culture and the consequent transnational impressions created by the medium about the Igbo character and his cultural allegiances. Through assessment of Igbo cultural motifs in domains of costume, makeup, and Igbo character portrayals in recently selected films, this work fingers Nol- lywood as responsible for the demeaned diasporic perceptions about Nigeria as well as the persistent Igbo cultural erosions. It concludes that while we give credit to Nollywood in areas of thematic render- ing of the Nigerian realities, the Igbo contextual (Igbo periodic and geographic settings) presentation is what this paper classes as pseudo-culture, a culture that betrays its source or what Ernest-Samuel Glo- ria refers to as “imitation of imitation.” It recommends among others, the privileging of a re-engineered mindset of filmmakers and cultural research in Igbo films to redeem the Igbo identity and possibly avert the UNESCO prediction of erosion of salient aspects of Igbo Culture by 2025.